University students and AIDS: Knowledge, attitudes and behavioral adjustment - Ajduković, Dean (Array, 1991)
This study addressed the relations between AIDS-related knowledge, attitudes, and behavior change among university students. A questionnaire covering such issues and personal background variables was administrated to 750 students at the University of Zagreb. Over-all, 62.7% of the knowledge items were answered correctly, while functional, self-protective aspects of knowledge proved to be much better than general knowledge. On the average, attitudinal responses were moderately liberal. Both self-reported change in risk-reduction behavior and personal concern due to the appearance of AIDS were very small. Correlations of risk-reducing behavior with permissive (.15) and restrictive (.14) attitude orientations and with general and functional knowledge (.08) were modest. The level of personal concern correlated neither with permissive attitudes nor with functional knowledge, while it correlated negatively with restrictive attitudes (-.20) and with general knowledge (-.08). Substantial association was only established between functional knowledge and permissive (.51) and restrictive attitude orientations (-.23). It is concluded that, in addition to knowledge and attitudes, a number of factors which restrain desired behavioral adjustment should be considered in anti-AIDS campaigns, such as perceived level of exposure to HIV in a particular environment, young age-specific illusion of invulnerability, peer norms, and others.